2020
DOI: 10.20482/jemm.2020.8.1.12
|View full text |Cite
|
Sign up to set email alerts
|

A Causal Analysis of Conglomerate Bankruptcies

Abstract: Purpose-Strategic causes for the failure include unrealistic growth, overexpansion, unfamiliar new markets, volume obsession, unrealistic promises and poor project selection. Organizational causes are insufficient capital and profits, lack of business knowledge, poor financial management, poor sales skills, inadequate marketing, poor leadership, poor leadership transfer, project losses, poor field performance and owner bankruptcy. Uncontrollable causes include industry and economic weakness and banking and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…According to Amankwah-Amoah [49], the entrepreneurs' failure was due to overexpansion. Similarly, KU and Whang [50] investigated conglomerate failures and concluded that, among other things, overexpansion and unrealistic growth were major causes of failure. Previously, the failure of entrepreneurs was largely explored in economics and finance literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Amankwah-Amoah [49], the entrepreneurs' failure was due to overexpansion. Similarly, KU and Whang [50] investigated conglomerate failures and concluded that, among other things, overexpansion and unrealistic growth were major causes of failure. Previously, the failure of entrepreneurs was largely explored in economics and finance literature.…”
Section: Discussionmentioning
confidence: 99%
“…Amankwah-Amoah [49] attributed organizational failure to overexpansion. Similarly, KU and Whang [50] studied conglomerate failures and concluded that overexpansion and unrealistic growth were prominent factors for failure, among other factors. Therefore, we propose the following hypothesis: Hypothesis 4 (H4).…”
Section: Growth and Overexpansion And Entrepreneurs' Failurementioning
confidence: 99%